The Reformed Church in Africa’s Laudium Declaration. A gift to the ecumenical community - De Beer, PJP (Nederduitse Gereformeerde Teologiese Tydskrif, 2013)
The author provides a brief overview of the history of the Reformed Church in Africa (RCA), a church that is rooted in the South African Indian community, from its birth in 1968 till the present day. He then proceeds to discuss the content and the impact of the Laudium Declaration, which was adopted at the synod of the RCA in 1990. The declaration was widely welcomed in the RCA, defining the evangelical character of the church. The reaction of other churches in the Dutch Reformed Church Family to the Laudium Declaration is discussed, together with an appraisal of the role that the declaration may play in the current unification process in the Dutch Reformed Family in South Africa. The article ends with a heartfelt prayer that the declaration will be accepted as a gift from God not only by the Reformed churches in South Africa, but by the wider ecumenical community.